Lifting the Optical and Thermoelectric Properties of Mg2Si as a Function of Sn Incorporation—Potential Thermoelectric Materials. (29th July 2021) - Manjula, M.; Viswanathan, E.; Muthumari, M.; Pradheepa, K.; Dhivyabharathi, R.; Shalini, L.; Kuznetsov, Denis; Veluswamy, Pandiyarasan
Abstract : By means of Density Functional Theory (DFT) study, we have performed the structural, electronic, optical and thermoelectric properties calculations of tin doped Mg2 Si (Mg2 Si1−x Snx, x = 0, 0.125, 0.25, 0.5, 0.75, 0.875, 1) using Full Potential Linearized Augmented Plane Wave (FP-LAPW) Method. The DFT study yields satisfactory results for electronic and thermoelectric properties of Sn doped Mg2 Si compared with experimental values. With semiclassical Boltzmann transport theory, the transport properties of Mg2 Si and Sn doped Mg2 Si alloys has been investigated systematically. According to the calculated band structure, density of states and electron density, the parent Mg2 Si/Sn materials having indirect energy gap (Γ−x) with ionic bonding; Sn doped ternary combinations Mg2 Si1−x Snx, x = 0.125, 0.25, 0.5, 0.75, 0.875 having direct band gap (Γ−Γ) with a mixed covalent and ionic bonding nature. Band gap decreases linearly with the increase of Sn-concentration in each alloy system except for Mg2 Si0.75 Sn0.25 combination. The optical properties calculations have been performed for the energy range between 0–13.5 eV. The thermoelectric properties have been calculated for the temperature range 100 K to 800 K. Out of the five studied materials, Mg2 Si0.75 Sn0.25 found to be a better thermoelectric material with increased Power factor, Seebeck coefficient, electrical conductivity and corresponding thermal conductivity at high temperature range.